WASTE BANK AND COMMUNITY WELFARE IN SIDOARJO (MAQASHID SHARIA PERSPECTIVE) - Oktafia, Renny (IAIN Tulungagung, 2021)
The originality of this research is where previous studies only discussed waste banks from the green economy perspective of maqashid sharia, or discussed economic empowerment only, but in this study it combines all aspects of previous research. This study aims to describe the role of the Sumringah waste bank in improving people's welfare, where the indicator used is Maqashid Syariah. This research uses qualitative research methods, with a case study approach. The waste management system at the Sumringah Waste Bank applies the 3R principle (reduce, reuse, recycle), this aims to motivate the community and increase awareness about managing waste independently from the source, as well as implementing a people's economy. The results of the analysis obtained indicate that there is prosperity in terms of: 1) Spirituality, namely by increasing alms Jariyah (hifz ad-din), 2) fulfilling mental needs (hifz an-nafs), 3) understanding about waste management and environmental hygiene (hifz al-nafs). aql), 4) maintenance of offspring (hifz al-aql), 5) income (hifz al-maal). The implication is as a behavior changer for the community, economic empowerment and quality of life of its members.